Instrumented Trail-Making Task (iTMT) to Differentiate Persons with No Cognitive Impairment, Amnestic Mild Cognitive Impairment, Alzheimer’s Disease - Proof of Concept Study - Zhou, He (Gerontology, 2016)
BACKGROUND: Objective and time-effective tools are needed to identify motor-cognitive impairment and facilitate early intervention. OBJECTIVE: We examined the feasibility, accuracy, and reliability of an instrumented trail-making task (iTMT), using a wearable sensor to identify motor-cognitive impairment, among older adults. METHODS: Thirty subjects (age = 82.2+6.1 years, body mass index = 25.7+4.8 kg/m(2), female = 43.3%) in 3 age-matched groups, 11 healthy, 10 with amnestic mild cognitive impairment (aMCI), and 9 with Alzheimer’s disease (AD), were recruited. Subjects completed iTMT, using a wearable sensor attached to the leg, which translates the motion of the ankle into a human-machine interface. iTMT tests included reaching to 5 indexed circles on a computer screen by moving the ankle-joint while standing. iTMT was quantified by the time required to reach all circles in the correct sequence. Three iTMT tests were designed, including numbers (1-to-5) positioned in a fixed (iTMT(fixed)) or random (iTMT(random)) order, or numbers (1-to-3) and letters (A&B) positioned in random order (iTMT(number-letter)). Each test was repeated twice to examine test-retest reliability. In addition, the conventional trail-making task (TMT A&B), Montreal Cognitive Assessment (MoCA), and dual-task cost (DTC: gait-speed difference between walking alone and walking while counting backward) were used as references. RESULTS: Good-to-excellent reliability was achieved for all iTMT tests (ICC=0.742-0.836). Between-groups difference was more pronounced, when using iTMT(number-letter), with average completion time of 26.3±12.4s, 37.8±14.1s, and 61.8±34.1s, respectively, for healthy, aMCI, and AD groups (p = 0.006). Pairwise comparison suggested strong effect sizes between AD and healthy (d=1.384, p=0.001) and between aMCI and AD (d=0.923, p=0.028). Significant correlation was observed when comparing iTMT(number-letter) with MoCA (r=−0.598, p=0.001), TMT A (r=0.519, p=0.006), TMT B (r=0.666, p<0.001), and DTC (r=0.713, p<0.001). CONCLUSION: This study demonstrated proof of concept of a simple, safe, and practical iTMT system with promising results to identify cognitive and dual-task ability impairment among older adults, including those with aMCI and AD. Future studies need to confirm these observations in larger samples, as well as iTMT’s ability to track motor-cognitive decline over time.